Identification and characterization of the major pseudocoelomic proteins of the giant kidney worm, Dioctophyme renale - Giorello, Alejandra Nahili (2017)
Background: The giant kidney worm, Dioctophyme renale, is a debilitating and potentially lethal parasite that inhabits and destroys, typically host´s right kidney, and may also be found in ectopic sites. It is circumglobally distributed, mainly in dogs, and is increasingly regarded as a threat to other domestic animals and humans. There is little information on the parasite´s true incidence, or immune responses to it, and none on its biochemistry and molecular biology. Results: We characterised the soluble proteins of body wall, intestine, gonads and pseudocelomic fluid (PCF) of adult parasites. Two proteins, P17 and P44, dominate the PCF of both male and females. P17 is of 16,622 Da by mass spectrometry, and accounts for the intense red colour of the adult parasites. It may function to carry or scavenge oxygen and be related to the ´nemoglobins´ found in other nematode clades. P44 is of 44,460 Da and was found to associate with fatty acids by thin layer chromatography. Using environment-sensitive fluorescent lipid probes, P44 proved to be a hydrophobic ligand-binding protein with a binding site that is highly apolar, and competitive displacement experiments showed that P44 binds fatty acids. It may therefore have a role in distributing lipids within the parasites and, if also secreted, might influence local inflammatory and tissue responses. N-terminal and internal peptide amino-acid sequences of P44 indicate a relationship with a cysteine- and histidine-rich protein of unknown function from Trichinella spiralis. Conclusions: The dominant proteins of D. renale PCF are, like those of large ascaridids, likely to be involved in lipid and oxygen handling, although there is evidence of strong divergence between the two groups.